The study of the electrical activity of the rectus femoris muscle and its relationship to the momentum for takeoff beat overwhelming in volleybal - Abedullateef, Maher (Journal of Physical Education, 2014)
The study aimed to identify the top of the electrical activity of the muscle rectus femoris of the two men and the momentum of the two men for takeoff during the beating overwhelming volleyball and get to know the relationship between the top of the electrical activity of the muscle rectus femoris momentum of the two men for takeoff during the beating overwhelming Volleyball The study was conducted on a sample of ambition of the Air Force Club Volleyball Men for the season 2011/2012. ). اThe researcher used the descriptive approach my style Relations connectivity for being one of the most curricula suited to the nature of the research problem as Astkhm researcher some setups and Aladawat for the implementation of the search experience , including a the (EMG) and a the (FOOT SCAN) and some software to analyze the results of which (Dart Fish) pouch statistical (SPSS ) study has come to some conclusions , including: low summit electrical activity of the muscle rectus femoris of the two-step first and third in the stage approach , which impacted negatively on the transfer speed of the leg forward. high summit of the electrical activity of the muscle rectus femoris for the second step in the process of approaching that worked on the speed of the transfer of leg forward. low speed sprint three steps , which negatively affected the momentum for being heavily dependent on the speed of approach and in length